Structural violence, social suffering, and the COVID-19 syndemic: discourses and narratives on the margins of the state in Texas - Dove, Sophia Annette; Khan, Shamshad; Kline, Kimberly N. (Frontiers in Communication, 2024)
This study holds immense importance because while much research has been done in the past couple of years to study the effects of COVID-19, the way the pandemic impacted the everyday lives of vulnerable communities and decision makings at local levels, especially in South central Texas and the United States, is yet to be known. Indeed, there remains a huge gap in an otherwise burgeoning literature on COVID-19 that could help illuminate the tensions between multiple and intersecting layers of marginalities (and vulnerability) of the communities on the margins of the state, on the one hand, and the one-size-fits-all official response at the national or state level on the other. Drawing on critical theoretical lens, document analysis, and in-depth interviews, our research aims to fill this gap as it also unravels narratives, experiences, and challenges faced and shared by local council members, public health professionals, and non-profit organizations who struggled to address the needs of their community in the face of larger social, political, and structural constraints.We first begin by discussing the literature on structural inequities and violence as a way to contextualize and better understand the impact of the COVID-19 pandemic on socially disadvantaged populations.As the COVID-19 pandemic unfolded at the global, national, and local levels, it cast a striking light on the existing structural inequities in societies. Structural inequities, primarily resulting from systemic racism, sexism, classism, ableism, and other inhibiting factors, are known to create specific social, economic, and cultural conditions that produce and exacerbate health inequities in society.Structural inequities, associated with poverty, marginalization, and vulnerability, can be seen as forms of violence that are embodied and experienced by people and that result in significant injuries, disabilities, and illnesses, causing immense human and social sufferings (Farmer et al., 2006;Singer & Rylko-Bauer, 2021).